2018
DOI: 10.1007/s10569-018-9860-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of “jumping” Trojans: a perturbative treatment

Abstract: The term "jumping" Trojan was introduced by Tsiganis et al. (2000) in their studies of long-term dynamics exhibited by the asteroid (1868) Thersites, which had been observed to jump from librations around L 4 to librations around L 5 . Another example of a "jumping" Trojan was found by Connors et al. (2011): librations of the asteroid 2010 TK7 around the Earth's libration point L 4 preceded by its librations around L 5 . We explore the dynamics of "jumping" Trojans under the scope of the restricted planar el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Presence of MMR may lead to the so-called adiabatic chaos (Wisdom 1985), which is caused, roughly speaking, by small quasi-random jumps between regular phase trajectories in certain parts of the phase space, where adiabatic approximation is violated. Applying systematically Wisdom's ideas to study of MMRs (Sidorenko 2006;Sidorenko et al 2014;Sidorenko 2018), we found that adiabatic chaos often coexists with the quasi-probabilistic transitions between specific phase regions. Both phenomena occur in that part of the phase space, where the "pendulum" or first-order Second Fundamental Model for Resonance (Henrard and Lamaitre 1983) approximations fail, because the first harmonic in the disturbing function Fourier series is not dominant.…”
Section: Introductionmentioning
confidence: 86%
“…Presence of MMR may lead to the so-called adiabatic chaos (Wisdom 1985), which is caused, roughly speaking, by small quasi-random jumps between regular phase trajectories in certain parts of the phase space, where adiabatic approximation is violated. Applying systematically Wisdom's ideas to study of MMRs (Sidorenko 2006;Sidorenko et al 2014;Sidorenko 2018), we found that adiabatic chaos often coexists with the quasi-probabilistic transitions between specific phase regions. Both phenomena occur in that part of the phase space, where the "pendulum" or first-order Second Fundamental Model for Resonance (Henrard and Lamaitre 1983) approximations fail, because the first harmonic in the disturbing function Fourier series is not dominant.…”
Section: Introductionmentioning
confidence: 86%
“…Trojans can jump from librating around L 4 to librating around L 5 and vice versa (see e.g. Tsiganis, Dvorak & Pilat-Lohinger 2000;Connors et al 2011;Sidorenko 2018). If λ r does not oscillate around a certain value, we have a passing object whose position relative to the host planet is not controlled by the 1:1 mean-motion resonance .…”
Section: Data a N D M E T H O D Smentioning
confidence: 99%
“…This kind of semianalytical procedure is now widely used for resonant problems in celestial mechanics involving high eccentricities and/or high inclinations (see e.g. Milani and Baccili 1998;Gallardo 2006aGallardo ,b, 2019bSidorenko 2006Sidorenko , 2018Saillenfest et al 2016;Saillenfest and Lari 2017;Pichierri et al 2017;Batygin and Morbidelli 2017). We note that the evolution of the pair (U, u) is secular by nature (frequency ∝ ε P ), whereas the evolution of the pair (Σ, σ) is semi-secular (frequency ∝ √ ε P ).…”
Section: The Resonant Coordinatesmentioning
confidence: 99%
“…We will recall here the method proposed by Henrard (1990Henrard ( , 1993 and applied to the trans-Neptunian region by Saillenfest et al (2016Saillenfest et al ( , 2017b and Saillenfest and Lari (2017). We will also discuss its variant introduced independently by Wisdom (1985) and used for instance by Sidorenko (2006Sidorenko ( , 2018. Section 5.1 presents the change of coordinates used to isolate the resonant angle and compute a semiaveraged Hamiltonian.…”
Section: Mean-motion Resonances With the Giant Planetsmentioning
confidence: 99%